199k views
1 vote
What is the simplified form of the rational expression below 5x2-5/3x2+3x

2 Answers

3 votes

Answer:

(5(x-1))/3x

Explanation:

User Mehyar Sawas
by
6.8k points
1 vote

Answer:


(5(x-1))/(3x)

Explanation:

The given expression is


(5x^(2) -5)/(3x^(2)+3x)

To simplify this rational expression, we need to extract the greatest common factor of each part,


(5x^(2) -5)/(3x^(2)+3x)=(5(x^(2)-1) )/(3x(x+1))

Then, we observe that the numerator has a difference of two perfect squares, which can be factored as


a^(2) -b^(2) =(a-b)(a+b)

Where,
a=x and
b=1


x^(2) -1=(x-1)(x+1)

Now, we applied this to the rational expression


(5x^(2) -5)/(3x^(2)+3x)=(5(x^(2)-1) )/(3x(x+1))=(5(x-1)(x+1))/(3x(x+1))=(5(x-1))/(3x)

Therefore the simplified form of the given expression is


(5(x-1))/(3x)

User Doug Hays
by
6.4k points